Drought tolerance of some bread and durum wheat vareities during germination - Tawfiq, Sherwan I.; Muhammed, Sanarya R.; Ahmed, Rozhgar Mustafa (Journal of Kerbala for Agricultural Sciences, 2018)
A laboratory experiment was conducted in Phytochemistry lab., Field Crop Science Department, College of Agriculture, University of Sulaimani during summer season of July to August, 2009. This factorial experiment conducted in a Randomized Complete Design with three replications, the factors are: the first was two species of wheat, Bread Wheat Triticum aestivum : Tammuz, Rabiaa, Rizgary, Sham-6 and Aras, and Durum Wheat Triticum durum: Acsad, Seminto, Crezo, Ovanto and Sham-3 and the second factors was five salt solutions 5000, 10000, 15000, 20000 and 25000 ppm. Various morpho-physiological parameter germination percentage, root length, shoot length, mean germination time were studied. From the results it was observed that Rabbia variety was the mostly drought tolerant among the other bread wheat varieties having significant effect of most germination attributes, Sham-3 variety gave maximum values of germination % and radicle length, while maximum coleoptile length, coefficient of velocity of germination% and minimum days required to germination recorded by Crezo variety. For both bread and durum wheat, the highest values of most germination attributed were obtained by treatment of control. Concerning the interaction between both of bread and durum wheat varieties and NaCl concentration, Tammuz variety with the treatment of control gave maximum values for most characters, while the interaction between Rabbia variety and 20000ppm NaCl recorded minimum days needed to germination. But regarding mean germination time character, interaction of Acsad, and Sham-3 with control treatment gave maximum value. In which all other values of germination attributes were 0.00 for 10000, 15000, 20000 and 25000ppm salt concentration, because all durum wheat varieties had not tolerant for drought condition.